Institutional Independence and the Effectiveness of the Regional Representative Council of The Republic of Indonesia Powers in the Formulation of the State Budget Law - Iswan (Indonesian Journal Publisher, 2026)
This study examines the relationship between institutional independence and the effectiveness of the Regional Representative Council’s authority in the formulation of the State Budget Law. The main issue lies in the limitations of the Regional Representative Council’s authority, which results in its limited influence in the legislative process. This study employs a normative legal approach, involving an analysis of legislation, constitutional theory, and relevant literature. The findings indicate that the limitations on the effectiveness of the Regional Representative Council’s authority are not only due to normative aspects but also to the weakness of institutional independence within the constitutional structure. In this context, the existing institutional design has not been able to create an effective mechanism for the balance of power. Therefore, strengthening the role of the Regional Representative Council requires a reconstruction of the institutional design capable of systematically integrating authority, independence, and effectiveness within the national legislative system.